EFFECT OF NPM, EPS, ROE, AND PBV ON STOCK PRICES - Fathihani, Fathihani (Dinasti International Journal of Management Science, 2020)
This study aims to analyze the effect of Net Profit Margin, Earning Per Share, Return on Equity, and Price to Book Value on stock prices. The population of this study are all companies that have been listed on the Indonesia Stock Exchange LQ-45 in the 2015-2018 research period. LQ45 index as one of the stock index indicators on the IDX can be used as a reference as a material to assess the performance of stock trading. This research is to determine the phenomenon that stock prices are one of the measurement tools used to provide information about the success of managing a company. This study uses secondary data in the form of annual financial reports obtained from the Indonesia Stock Exchange. The sampling technique was taken by using purposive sampling as many as 28 companies. Analysis of the data used is multiple linear regression. From these results it can be concluded that earnings earnings have a significant positive effect on stock prices, Return on equity has a significant negative effect, Price to book value has a significant positive effect on stock prices, net profit margins have a negative and no significant effect on stock prices